Positioning relapse and recovery through a cultural lens of desire: A South Australian case study of disordered eating. (August 2018) - Musolino, Connie; Warin, Megan; Gilchrist, Peter
This article explores how desire operates in the daily lives of women with disordered eating. Based on qualitative findings from a South Australian study investigating why women with disordered eating are reluctant to seek help, we trace the multiple "tipping points" and triggers that are central to participants' everyday experiences. Employing anthropological interpretations of desire, we argue that triggers are circulations of productive desire, informed by cultural values and social relations, and embodied in routine daily acts. We examine the cultural-work of desire and the ways in which gendered relationships with food, eating and bodies trigger desires, creating a constant back and forth movement propelling participants in multiple directions. In conclusion, we suggest that a socio-cultural approach to desire in disordered eating has clinical implications, as cultural configurations of desire may help to understand ambivalence towards relapse and recovery.